1964
DOI: 10.1111/j.2042-7158.1964.tb07505.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tyramine on a spinal reflex in the anaesthetised chick

Abstract: The effects of tyramine on polysynaptic spinal reflexes in anaesthetised chicks and cats have been studied. Very large intravenous doses of tyramine depressed the reflexly evoked contractions of skeletal muscles by an action exerted in the spinal cord. Since tyramine is normally present in the central nervous system, its function may be to exert some inhibitory controlling influence on muscular activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1967
1967
1977
1977

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Bowman and et al (1964) found that strychnine was more active, the younger the chick, i.e. the smallest effective dose in a 1-day-old chick was about 1-2 u,g.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Bowman and et al (1964) found that strychnine was more active, the younger the chick, i.e. the smallest effective dose in a 1-day-old chick was about 1-2 u,g.…”
Section: Resultsmentioning
confidence: 97%
“…The effect of strychnine in both anesthetized and intact conscious young chickens and spinal reflexes has been studied in detail (Bowman et al, 1964;Osuide, 1968Osuide, , 1972. Bowman and et al (1964) found that strychnine was more active, the younger the chick, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bowman et al (1964) showed that strychnine was the more active, the younger the chicken: the smallest effective dose of strychnine was about 1-2 /ig. intravenously in 1-day-old chickens, while 15-20 /Jig.…”
Section: B Central Nervous Systemmentioning
confidence: 97%
“…Maximal twitches Twitches of the gastrocnemius or tibialis interior were elicited at a frequency of 01 Hz by stimulation of the peripheral portion of the severed ipsilateral sciatic nerve with rectangular shocks of 01 ms duration and of about twice the strength required to evoke a maximal twitch (Bowman et al, 1964).…”
Section: Methodsmentioning
confidence: 99%